Implementasi Administrasi Sederhana Pada Kegiatan Sadar Wisata Bersih Pantai (Coastal Cleanup) Di Gili Asahan Lombok Barat NTB - Basuki Srihermanto; Siti Yulianah M Yusuf; Nia Kurniati; Syaumudinsyah; Fitriah Kartini (CV. Multi Kreasi Media, 2023)
The community service activity entitled Implementation of Simple Administration in the Coastal Cleanup Tourism Awareness activity in Gili Asahan, West Lombok, NTB is aimed at empowering the capacity of higher education institutions in an effort to increase the community's ability to utilize science to carry out simple recording (administration) in beach cleaning activities as a form of realizing Tourism Awareness. This beach clean-up activity was carried out by representatives of STIA Mataram lecturers, STIA Mataram students together with tourism activists such as Hotels, Bungalaws, Cafés together with community members around Gili Asahan. This STIA Mataram Community Service provides two benefits, the first is the implementation of simple administration on beach cleaning activities and the second benefit in the form of beach cleaning activities. The method used is coaching, technical guidance and direct application using computer media for implemented administrative activities. Then beach clean-up activities were carried out in the form of direct action along Gili Asahan beach. at the cleaning location, namely along Gili Asahan beach. The rubbish on Gili Asahan is rubbish carried by the waves, so rubbish will always be there at all times on Gili Asahan so rubbish must always be cleaned from the beach. As a result of this community service, a stretch of coastline that is clean, neat and beautiful is formed, it is hoped that it will attract the interest of foreign tourists to visit. Another result obtained from this community service is the ability of policy makers in policy management, in this case the RT 5 Gili Asahan Village staff who received simple administrative information in managing this beach cleaning activity. Remembering the importance of this community service because it can provide support and guidance for the community carrying out beach cleaning activities as well as providing information for stakeholders regarding the implementation of beach cleaning as a tourism awareness movement on Gili Asahan who will carry out similar actions in the future.